Assessing materials development: An expert evaluation of instructional materials developed by pre-service English teachers - Sukarno; Hidayati, Sari; Fitrianingsih, Ihtiara; Widiyati , Dewi Nur; Azhra , Shabrina Yumna; Jinabe , Megan; Wulandari , Fitriya Dessi; Dyastuti, Herwin; Karima , Kauna; Tama , Adivta Yudha; Jannah , Nita Maghfiratul; Gharamah, Fadhl Mohammed Awadh; Alsamiri, Yasir A. (Universitas Ahmad Dahlan, 2026)
The ability of pre-service English teachers to create high-quality, contextually appropriate instructional materials is a critical component of effective pedagogy. This study provides a quantitative and analytical assessment of their proficiency in instructional design. By evaluating 28 material packages developed by pre-service teachers, this study identifies their strengths and remaining challenges in implementing modern pedagogical principles. A panel of ten subject experts evaluated the materials using a validated rubric assessing curriculum alignment, relevance, higher-order thinking skills (HOTS), and 21st-century skills. The results revealed variation in design competencies, with pre-service teachers performing best in foundational areas such as curriculum alignment (mean score 7.875) and pedagogy (mean scores for Suitability and 21st-century skills were 7.679 and 7.357, respectively). However, the study also found challenges in applying advanced pedagogical concepts, such as HOTS, Industry 4.0, and Society 5.0, with mean scores of 7.000, 7.000, and 6.964, respectively. These findings suggest an area for further strengthening in teacher education programs, particularly in supporting the integration of complex, abstract concepts like HOTS and contemporary pedagogical frameworks. Without sufficient preparation in these areas, pre-service teachers may find it challenging to apply these concepts effectively in their instructional practice.